Perencanaan Geometrik Simpang Tiga Dan Sinyal Lalu Lintas (Studi Kasus Evaluasi Simpang Rimbo, Kota Jambi) - T, Riki; Yamali, Fakhrul Rozi; Setiawan, Ari (Jurnal Civronlit Unbari, 2024)
Jambi City is a city that is developing rapidly in various fields. To support this aspect, various supporting facilities are needed, one of which is good physical and non-physical infrastructure. Physical infrastructure includes facilities and infrastructure, and use management. The need for physical infrastructure is very important to support easy accessibility of activities and developments in urban areas. Highway planning and construction is one of the factors in the formation of sustainable areas, including the type of infrastructure development that serves community needs, including the process of opening up traffic space to connect one area to another. The aim of this research is to analyze the traffic movement of Simpang Rimbo at each arm of the intersection and to find out the level of traffic flow service on the road sections at the intersection of the three West Ring Road-3, Jalan Captain Pattimura, and Jalan Mandalo. The research method is to evaluate existing traffic signals and their relationship to road geometric planning. The results of this research are an evaluation and analysis of the geometric planning of traffic signals planned to lower the LOS value, meaning increasing the level of service at the Rimba intersection in the next 10 years.